PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG - Bregas Wirotomo; Tarmizi Achmad (Diponegoro Journal of Accounting, 2018)
This study aims to analyze the application of corporate governance as an independent variable to the audit report as a dependent variable.This study uses secondary data obtained from CGPI reports. This study used 83 companies replicated in the implementation of good corporate governance conducted by The Indonesian Institute for Corporate Governance (IICG) in the form of rating of Corporate Governance Perception Index (CGPI) and listed on the Stock Exchange 2012-2016. This research used purposive sampling method. The statistical technique used in this study is multiple regression.The results obtained from this study indicate good corporate governance, having a negative significance in the lag audit report.